Structures of proline-rich peptides bound to the ribosome reveal a common mechanism of protein synthesis inhibition - Matthieu G. Gagnon; Raktim N. Roy; Ivan B. Lomakin; Tanja Florin; Alexander S. Mankin; Thomas A. Steitz (2016)
With bacterial resistance becoming a serious threat to global public health, antimicrobial peptides (AMPs) have become a promising area of focus in antibiotic research. AMPs are derived from a diverse range of species, from prokaryotes to humans, with a mechanism of action that often involves disruption of the bacterial cell membrane. Proline-rich antimicrobial peptides (PrAMPs) are instead actively transported inside the bacterial cell where they bind and inactivate specific targets. Recently, it was reported that some PrAMPs, such as Bac71–35, oncocins and apidaecins, bind and inactivate the bacterial ribosome. Here we report the crystal structures of Bac71–35, Pyrrhocoricin, Metalnikowin and two oncocin derivatives, bound to the Thermus thermophilus 70S ribosome. Each of the PrAMPs blocks the peptide exit tunnel of the ribosome by simultaneously occupying three well characterized antibiotic-binding sites and interferes with the initiation step of translation, thereby revealing a common mechanism of action used by these PrAMPs to inactivate protein synthesis. Our study expands the repertoire of PrAMPs and provides a framework for designing new-generation therapeutics.